Marx/Bourdieu: Convergences et Tensions, entre Sociologie Critique et Philosophie Politique de L’émancipation - Corcuff, Philippe (جامعة زيان عاشور الجلفة, 2023)
This text proposes a partial confrontation between the critical thoughts of Karl Marx and Pierre Bourdieu within the framework of a new exploratory hermeneutic of theoretical texts deviating from the presupposition of coherence of “works” and “authors” in the wake of Michel Foucault’s warnings in The Archaeology of Knowledge (1969). On the basis of the dismemberment of concepts and methods in relation to the “works” from which they are derived, it is a question of creating renewed sparks of knowledge. To do this, will be kept away from systematic reconstructions called “marxism” or “bourdieusism”. Four fields are then cleared. The first field concern the methodology of the social sciences in the relationship between the observed concrete and the theoretical abstraction. The second field concerns the sociology of social classes between objectivism and constructivism. Bourdieu’s “structuralist constructivism” and Marx’s hesitations between economism and constructivism are then compared. The third field concerns the theory of praxis between sociology of action and revolutionary politics. The fourth field concerns the political philosophy of emancipation, important in Marx’s approach, present but more marginal in Bourdieu in a spinozist inspiration putting forward the knowledge of determinisms.
Keywords: ماركس، كارل هانريش، ت. 1883 م. -- بورديو، پيير، ت. 2002 م. -- علم الاجتماع النقدي -- الفلسفة السياسية -- الطبقات الاجتماعية